2012
DOI: 10.7778/jpkm.2012.26.4.051
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study on the Effect of Hwangryunhaedock-tang on Atopic Dermatitis

Abstract: ObjectivesThe purpose of this study is to evaluate the effect of Hwangryunhaedock-tang on Atopic Dermatitis MethodsThis study population was 71 pediatric allergic rhinitis patients who had been treated in OO hospital. All the patients were asked to answer the questionnaire consisting of 8 questions about symptoms of atopic dermatitis. Results 1.The total scores from the same questionnaire about atopic dermatitis symptoms were significantly improved after the treatment compared to the scores before the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Orengedokuto also attenuates the inflammatory symptoms in mite-induced allergic dermatitis [9] and chemical allergen-induced contact dermatitis [10,11]. In addition to our report [8], berberine also exerts an anti-inflammatory effect in 12-O-tetradecanoylphorbol-13-acetate-induced dermatitis [12], allergic contact dermatitis [13,14] and fungus-induced dermatitis [5] in animals. These findings suggest that berberine (or Orengedokuto) is effective against inflammatory skin diseases.…”
Section: Tsugunobu Andoh and Tadamichi Shimizusupporting
confidence: 66%
See 1 more Smart Citation
“…Orengedokuto also attenuates the inflammatory symptoms in mite-induced allergic dermatitis [9] and chemical allergen-induced contact dermatitis [10,11]. In addition to our report [8], berberine also exerts an anti-inflammatory effect in 12-O-tetradecanoylphorbol-13-acetate-induced dermatitis [12], allergic contact dermatitis [13,14] and fungus-induced dermatitis [5] in animals. These findings suggest that berberine (or Orengedokuto) is effective against inflammatory skin diseases.…”
Section: Tsugunobu Andoh and Tadamichi Shimizusupporting
confidence: 66%
“…In cases of atopic dermatitis with severe cutaneous inflammation and pruritus, Orengedokuto improves several symptoms [5,6].…”
Section: Therapeutic Effect Of Orengedokuto and Berberine In Inflamma...mentioning
confidence: 99%
“…HLJDT is known to possess therapeutic effects of clearing heat and detoxification in Chinese medicine practice and is widely used in skin diseases, such as eczema and AD ( Chen GR. et al, 2016 ; Ko and Baek, 2012 ; Yang et al, 2017 ). HLJDT is composed of four Chinese medicines, including Coptis chinensis Franch (Huanglian, whose rootstocks have medicinal use), Scutellaria baicalensis Georgi (Huangqin, whose root has medicinal use), Phellodendron amurense Rupr.…”
Section: Introductionmentioning
confidence: 99%
“…HLJDD is a well-known written prescription for alleviating inflammatory conditions in the theory and practices of Chinese medicine because of the function of clearing body fire and removing heat toxicity [1] . Previous clinical studies have documented that HLJDD showed potent therapeutic effects on various inflammatory diseases including atopic dermatitis (AD) [2] , [3] , [4] . In addition, our previous work [5] also demonstrated that HLJDD has strong anti-inflammatory and anti-allergic activities in in vivo and in vitro models of AD.…”
Section: Introductionmentioning
confidence: 99%